A tabu search heuristic for the bi-objective star hub location problem. Issue 3 (2nd July 2020) - Ghaffarinasab, Nader
ABSTRACT: In this paper, we address the bi-objective star hub location problem that has applications in logistics and telecommunications networks design. Two well-known objectives concerning cost and service level criteria, namely the median and center objectives are considered simultaneously. The first objective tries to minimize the total transportation cost, while the second one aims at minimizing the length of the longest path between the O/D pairs. The problem is formulated as a bi-objective MIP model which in turn is converted to a single objective problem by aggregating the two objective functions using a weighting method. In order to solve the proposed model, an efficient Tabu Search (TS) heuristic is developed. Extensive computational experiments are conducted to examine the efficiency of the proposed mathematical model as well as the TS algorithm and to study the effect of different input parameters on the final solutions. Moreover, using different values for the weights of the objective functions, Pareto-optimal solutions are obtained for the problem and the corresponding efficient frontiers are plotted.